Randomised clinical trial: palliative long‐term abdominal drains vs large‐volume paracentesis in refractory ascites due to cirrhosis. Issue 1 (1st June 2020) - Macken, Lucia; Bremner, Stephen; Gage, Heather; Touray, Morro; Williams, Peter; Crook, David; Mason, Louise; Lambert, Debbie; Evans, Catherine J.; Cooper, Max; Timeyin, Jean; Steer, Shani; et al.
Summary: Background: Palliative care remains suboptimal in end‐stage liver disease. Aim: To inform a definitive study, we assessed palliative long‐term abdominal drains in end‐stage liver disease to determine recruitment, attrition, safety/potential effectiveness, questionnaires/interview uptake/completion and make a preliminary cost comparison. Methods: A 12‐week feasibility nonblinded randomised controlled trial comparing large‐volume paracentesis vs long‐term abdominal drains in refractory ascites due to end‐stage liver disease with fortnightly home visits for clinical/questionnaire‐based assessments. Study success criteria were attrition not >50%, <10% long‐term abdominal drain removal due to complications, the long‐term abdominal drain group to spend <50% ascites‐related study time in hospital vs large‐volume paracentesis group and 80% questionnaire/interview uptake/completion. Results: Of 59 eligible patients, 36 (61%) were randomised, 17 to long‐term abdominal drain and 19 to large‐volume paracentesis. Following randomisation, median number (IQR) of hospital ascitic drains (long‐term abdominal drain group vs large‐volume paracentesis group) were 0 (0‐1) vs 4 (3‐7); week 12 serum albumin (g/L) and serum creatinine (μmol/L) were 29 (26.5‐32.5) vs 30 (25‐35) and 104.5 (81‐115.5) vs 127 (63‐158) respectively. Total attrition was 42% (long‐term abdominal drain group 47%, large‐volume paracentesis group 37%). Median (IQR) fortnightly community/hospital/social care ascites‐related costs and percentage study time in hospital were lower in the long‐term abdominal drain group, £329 (253‐580) vs £843 (603‐1060) and 0% (0‐0.74) vs 2.75% (2.35‐3.84) respectively. Self‐limiting cellulitis/leakage occurred in 41% (7/17) in the long‐term abdominal drain group vs 11% (2/19) in the large‐volume paracentesis group; peritonitis incidence was 6% (1/17) vs 11% (2/19) respectively. Questionnaires/interview uptake/completion were ≥80%; interviews indicated that long‐term abdominal drains could transform the care pathway. Conclusions: The REDUCe study demonstrates feasibility with preliminary evidence of long‐term abdominal drain acceptability/effectiveness/safety and reduction in health resource utilisation. Trial registration: ISRCTN30697116, date assigned: 07/10/2015.